Distribution Of Abo Blood Groups In Acute Leukemia Patients In Sulaymaniyah, Kurdistan Region Of Iraq (Applied Biological Research, 2022)
Leukemia is the most diagnosed form of cancer that attacks adults and  children. It is a heterogeneous group of acquired clonal hematological  malignancies that incorporates diverse biologically distinct subgroups. The  aim of present study was to assess the distribution of different blood groups  in acute leukemia patients of Kurdish Iraq’s. This retrospective descriptive study was conducted on 533 patients who visited Hiwa Cancer Hospital,  Sulaymaniyah, Kurdistan region, Iraq from January 2015 to December  2020. The age, gender, and leukemia type along ABO blood groups were  determined. Overall, 533 acute leukemia patients, including acute lymphatic  eukemia (ALL) and acute myeloblastic leukemia (AML), were diagnosed.  There were 316 male and 217 female patients (ratio 1.46:1), with the age  range >1 to 102 years. The study showed that in 5.6% patients none of the  blood types were registered. Similarly, the ABO blood group distributions  were 186 (34.9%) O, 156 (29.3%) A, 131 (24.6%) B, and 30 (5.6%) AB. All the groups A, AB, and O were positively and significantly related to acute  leukemia. From beta coefficient value O group was found more vulnerable  to ALL and AML at 0.444 and 0.445, respectively.
Keywords: ABO blood group; leukemia; Iraq